(untitled) (AmeriQuests)
By way of introduction to this issue, which features work by Thomas Spijkerboer that investigates parallels between evictions of irregularized persons in Apartheid South Africa and contemporary Europe, as well as a portfolio of commentaries and a set of book reviews on current work in the field, Robert Barsky offers a reflection on a new project aimed at studying the first few minutes of an encounter between vulnerable migrants and a host country officials.